(untitled) (Research, Society and Development, 2022)
This article analyzes the various legal tools that aim to guarantee the inclusion and accessibility of deaf subjects in regular public education in Belém do Pará, emphasizing the analysis in History Teaching based on signed reports of deaf university students, who have already gone through teaching- learning of the subject “History”. The objective is to understand how the reality of education and history classes happens or happened for the deaf subjects interviewed. The main research question is: did you find it difficult to understand the subjects of History? This is a field research with graduates of the public school system, in addition to being based on reports from authors in the literature. According to the interviews carried out, the results indicate that the lack of accessibility and inclusive practices during classes negatively affected the understanding of deaf students in History subjects.